2002
DOI: 10.1037/0096-3445.131.4.477
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of categorical color perception: A perceptual learning approach to the linguistic relativity hypothesis.

Abstract: Color perception can be categorical: Between-category discriminations are more accurate than equivalent within-category discriminations. The effects could be inherited, learned, or both. The authors provide evidence that supports the possibility of learned categorical perception (CP). Experiment 1 demonstrated that observers' color discrimination is flexible and improves through repeated practice. Experiment 2 demonstrated that category learning simulates effects of "natural" color categories on color discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
142
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(177 citation statements)
references
References 60 publications
(123 reference statements)
13
142
2
1
Order By: Relevance
“…Furthermore, recent investigations of categorical perception Ozgen & Davies, 2002) have produced results favoring a verbal locus for perceptual memory judgments. found that effects attributed to categorical perception (better cross-category than within-category discrimination) disappeared under verbal interference and Özgen and Davies (2002) found that novel category boundaries may be established by common labels (see also Özgen, 2004Özgen, , Goldstone, 1994Özgen, , 1998. These results might suggest that categorical perception is based on a cross-category advantage in labeling and not a genuinely perceptual phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent investigations of categorical perception Ozgen & Davies, 2002) have produced results favoring a verbal locus for perceptual memory judgments. found that effects attributed to categorical perception (better cross-category than within-category discrimination) disappeared under verbal interference and Özgen and Davies (2002) found that novel category boundaries may be established by common labels (see also Özgen, 2004Özgen, , Goldstone, 1994Özgen, , 1998. These results might suggest that categorical perception is based on a cross-category advantage in labeling and not a genuinely perceptual phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The question of whether the language available to describe perceptual experience can influence the experience itself is one that continues to engender lively debate (Boroditsky, 2001;Guest & Van Laar, 2002;Özgen & Davies, 2002;Saunders & van Brakel, 2002). Historically, this debate was characterized by the dichotomous views that thought is either shaped by language (Ray, 1952;Brown, 1976) or completely independent of it (Berlin & Kay, 1969;Heider & Olivier, 1972).…”
mentioning
confidence: 99%
“…1C), but now every target color belonged to a different lexical category from the accompanying distractors. This training task is different from the perceptual learning paradigm of categorical color perception (28)(29)(30) in that we explicitly assigned a new linguistic term to each of the four stimulus colors: A, B, C, and D. Our interest is focused on subjects' responses to the color pairs that had been within-category before training but became between-category after training. The goal was to determine whether pairs of colors that were withincategory before training would be discriminated faster after training had assigned them to distinct linguistic categories, and if so whether the difference in speed of discrimination would be greater in the RVF than the LVF, revealing a lateralized Whorf effect on newly learned categories.…”
mentioning
confidence: 99%
“…It has been shown that perceptual discrimination can be trained to new category distinctions that will then produce observable CP effects (19,28,29). Özgen and Davies have shown specifically that category effects can be trained in the color domain, although they did not train explicitly verbal categories (30). If a lateralized category effect can be shown to occur for experimentally trained verbal categories, it will follow that the lateralized Whorf effect can occur even when the categories involved violate both universal tendencies in color naming and those of the language of the subjects.…”
mentioning
confidence: 99%
“…We present a model of the political economy of government spending that explains why a low level of social capital induces a lack of public investment and thereby reduces long-run growth. We derive the dynamic general equilibrium of an economy in which the government provides both 1 Linguists have argued that some components of culture may have had an e¤ect on speci…c dimensions of language (Boroditsky 2000;Ozgen and Davies 2002;Zhoua et al 2010). In particular, languages that forbid dropping the …rst person pronoun are associated with cultures that give more emphasis to the individual relative to the social context (Kashima and Kashima 1998).…”
Section: Introductionmentioning
confidence: 99%